EEG Correlates of Perceptual Reversals in Boring's Ambiguous Old/Young Woman Stimulus. (September 2014) - Kornmeier, Jürgen; Bach, Michael
Ambiguous figures attract observers because perception alternates between different interpretations while the sensory information stays unchanged. Understanding the underlying processes is difficult because the precise time instant of this endogenous reversal event needs to be known but is difficult to measure. Presenting ambiguous figures discontinuously and using stimulus onset as estimation of the reversal event increased temporal resolution and provided a series of well-confirmed EEG signatures. In the current EEG study we used this 'onset paradigm' for the first time with Boring's old/young woman stimulus. We found an early occipital event-related potential (ERP) correlate of reversals between the perception of the old woman and the perception of the young woman that fits well with previous ERP findings. This component was not followed by the often-reported occipito-parietal Reversal Negativity at 260 ms, but instead by an occipito-temporal N170, that is typically reported with face stimuli. We interpret our results as follows: Ambiguity conflicts take place during processing of stimulus elements in early visual areas roughly 130 ms after stimulus onset. The disambiguation of these elements and their assembly to object 'gestalts' result from an interplay between early visual and object-specific brain areas in a temporal window between 130 and 260 ms after stimulus onset. In the particular case of Boring's old/young woman the processes of element disambiguation and gestalt construction are already finished at 170 ms and, thus, 90 ms earlier than in the case of ambiguous geometric figures (eg Necker cube or Schroeder staircase) or of binocular rivalrous gratings.